A escrita colaborativa no google docs: uma intervenção pedagógica no ensino de língua inglesa - Dantas, Sabrina Guedes Miranda (Universidade Federal Rural do Semi-Árido, 2020)
The practice of writing in English in public High Schools is often restricted to translation tasks or repetitive exercises of grammatical structures. In this sense, we seek to develop a pedagogical intervention to teach English through Collaborative Writing on Google Docs for the mobilization of language practices in the digital universe with students from an Integrated High School Technical course at the Federal Institute of Education, Science and Technology of Rio Grande do Norte. To achieve this objective, we are grounded on the conceptions that language is social interaction and mediates human relations through discourse genres (BAKHTIN; VOLOCHÍNOV, 2006). This social interaction is at the heart of Vygotsky's Sociocultural Theory applied to Second Language Learning (LANTOLF; THORNE, 2007); serves as a mediator for learning and collaborative writing (SMITH; MACGREGOR, 1992; FUNG, 2006, 2010; ALLEN et al., 1987), and it is also the premise for the device chosen to operationalize the teaching proposal for Online Collaborative Writing (OCW) (YIM; WARSCHAUER, 2017; LEANDRO; WEISSHEIMER, 2017; EMILIANO, 2016; KESSLER; BIKOWSKI; BOGGS, 2012). The methodological approach of this study is a qualitative Pedagogical Intervention (RICHARDSON, 2016; DAMIANI et al., 2013) in which students wrote, collaboratively, a news post for an informational blog. 36 students participated of the intervention and they were divided into seven collaboration groups, that met for the writing of the text over three non-consecutively weeks. The corpus of this research consisted of the answers of the questionnaires applied before and after the intervention, the interactions on the chat, and the field notes of the teacher. Regarding the effects of the pedagogical intervention on the participants, we concluded that, students need more opportunities to improve the practice of group activities; social problems can make it difficult to use the digital tool; and English language learning was a consequence of OCW. With regard to chat interactions, in addition to finding all the characteristics of face-to-face CW, we detected one more related to factors of social and technical reason that may influence the performance of OCW. Regarding the evaluation of the intervention itself, we suggest the improvement of the teaching method by increasing the number of online meetings, the realization of the method by the discipline's teacher and the explicit instruction on collaborative practices
Keywords: Ensino; Língua inglesa; Escrita colaborativa online; Intervenção pedagógica; Tecnologia; Teaching; English language; Online collaborative writing; Pedagogical intervention; Technology; MULTIDISCIPLINAR::ENSINO